Global Competition, Local Unions, and Political Representation: Disentangling Mechanisms - Becher, Michael; Stegmueller, Daniel (SSRN, 2023)
While recent scholarship has demonstrated multiple political effects of international trade, less attention has been paid to unbundling the mechanisms through which import competition affects democratic politics. One mechanism, in theory, works through labor unions as domestic countervailing powers shaping legislative responses on compensation and trade votes. We assess the relevance of unions as a mediating variable in the US Congress. For identification, we leverage two distinct sources of exogenous variation, one instrument for import exposure and another for unionization, and combine them in a semiparametric estimator. We find that (i) import competition lowers district-level unionization, (ii) weaker unions lead to less legislative support for compensating economic losers and less opposition to trade deregulation, and (iii) the union mechanism represents a large fraction of the overall effect of import exposure on legislative votes. The results help explain weak compensation and further trade liberalization in the face of rising global competition.
Keywords: Political economy; Globalization; Unions; Representation; Causal mediation; Effect decomposition; US Congress; 59 Ciencia Política; ODS 10 - Reducción de las desigualdades